Biomechanical behaviour of temporomandibular joints during opening and closing of the mouth: A 3D finite element analysis. (22nd June 2020) - Shu, Jingheng; Ma, Hedi; Jia, Lirong; Fang, Hongyang; Chong, Desmond Y.R.; Zheng, Tinghui; Yao, Jie; Liu, Zhan
Abstract: Temporomandibular joints (TMJs) constitute a pair of joints that connect the jawbone to the skull. TMJs are bilateral joints which work as one unit in conducting daily functions such as speaking, mastication, and other activities associated with the movement of the jaw. Issues associated with the TMJs may arise due to various factors—one such factor being the internal load on the TMJ. These issues may contribute to temporomandibular disorders (TMD). This study aims to evaluate the mandibular trajectories and the associated stress changes during the process of opening the mouth on the TMJs of an asymptomatic subject. The mouth opening motion was recorded by a motion capturing system using models of the mandible and maxilla constructed based on the computed tomography (CT). Two discs constructed based on magnetic resonance imaging (MRI). Finite element analysis was performed on the relative motion of the mandible to the maxilla and validated. The process modelled by these displacements provided less than 10% error in terms of deformation. The simulation results indicate that the lateral intermediate zone—the head and neck of the mandible—and the articular eminence sustained the most significant stresses during the mouth opening motion. The results also suggested that the stresses increase as the range of opening increases with the greatest von Mises stress, tensile, and compressive stress found at the position of maximal opening. Abstract : A deformable maxillofacial system with a more relaxed initial mandibular position during mouth opening was analysed by finite element methods according to subject‐specific trajectories. The results indicated that with the mouth opening, the stress in temporomandibular joints increased slowly at the beginning but quickly as the condyles crossed the articular eminence. It also exhibited that the intermediated zone of disc sustained the most significant stress but it was a safe process for an asymptomatic subject.